Influenza Virus Evades NK Cell Responses by Enhancing Ly49:MHC-I Interactions - Mahmoud, Ahmad Bakur (Université d'Ottawa / University of Ottawa, 2016)
Natural killer (NK) cells are a type of innate immune cell that can identify and eliminate viral infected cells and cancer cells. NK cells express an array of inhibitory and activating receptors such as natural cytotoxicity receptors, the mouse Ly49 or human KIR family, and NKR-P1 family. The integration of signals that NK cells receive through these receptors controls their activation and ability to kill target cells. Both Ly49 and KIR recognize MHC-I molecules on healthy cells Ly49:MHC-I engagement is essential for functional NK cell development. In the absence of these interactions NK cell is consider as ‘uneducated’ or ‘unlicensed’. Ly49 receptor interactions with MHC-I are critical in an effective NK cell response against cancer. However, the role of unlicensed NK cells in NK-mediated control of viruses is poorly understood. Using NKCKD mice, we sought to determine how the loss of Ly49:MHC-I education, and the concomitant loss of inhibition via MHC-I, affected survival against influenza infection. In this study, we show that Ly49-deficient mice exhibit lower viral load and greater protection than WT mice when infected with influenza. However, this protection was lost when Ly49I was transgenically restored to these mice. Similarly, MHC-I-deficient mice, that also lack educated NK cells, were resistant to influenza infection, and lost this protection when NK cells were depleted before challenge. Based on the markedly reduced inflammation in the Ly49-deficient mice compared to the WT, we conclude that the Ly49-deficient NK cells are swifter and more effective in clearing influenza, resulting in less viral burden and consequentially less need for a dangerously aggressive inflammatory response. Furthermore, influenza infection enhanced MHC-I expression on lung epithelial cells, which could be responsible for inhibition of NK cells. Consequently, blockade of inhibitory Ly49C/I receptors protected WT mice from lethal influenza infection. Additionally, Perforin-deficient NKCKD succumbed to the infection demonstrating that NK cell directly eliminate influenza-infected cells. Collectively, these results confirm that influenza is capable of inhibiting NK cells through MHC-I engagement of KIR/Ly49, and suggests that blocking this interaction may provide a viable therapeutic avenue for severe influenza cases. these results challenge our understanding of basic NK cell function and suggest that, rather than subdividing NK cells into ‘licensed’ and ‘unlicensed’ based on their expression of self-specific Ly49 receptors, a more accurate depiction of these NK subsets would be ‘cancer-specialized’ and ‘pathogen-specialized’. While further work is required to fully test this paradigm of cancer- and pathogen-specialized NK cells, I hope that my findings will stimulate a new appreciation for the role of NK cells in virus control, and lead to a better understanding of this critical immune cell.
Keywords: influenza; NK cells; unlicensed NK cells; Ly49 receptor